A small New Keynesian model to analyze business cycle dynamics in Poland and Romania - Valeriu Nalban (Contemporary Economics, 2015)
In this paper, we derive a small textbook New Keynesian DSGE model to evaluate Polish and Romanian business cycles during the 2003 - 2014 period. Given the similarities between the two economies, we use an identical calibration procedure for certain coefficients and marginal prior distributions for the others, rendering the resulting cross-country differences as primarily data-driven. The estimated structural coefficients for the two countries have comparable values, implying similar qualitative macroeconomic transmission mechanisms. However, the Romanian shocks display much more variability, and the impulse response functions have similar shapes but deeper trajectories. The model-simulated theoretical moments for the output growth, the inflation rate and the nominal interest rate (means, standard deviations and cross-correlations) are close to their actual data counterparts, demonstrating the models' ability to match and replicate statistical properties of the observed variables. Shock decompositions of the output and the inflation rate revealed the driving forces of the business cycles; demand shocks explain much of the GDP growth dynamics (persistent positive contributions before the crisis and negative thereafter), whereas prices were also driven by supply and monetary policy shocks, the latter being more important for Poland.
Keywords: C11; C32; E32; 330; New-Keynesian model; DSGE; business cycle; Bayesian estimation; shock decomposition